Volatile organic compounds pollution control technologies: Past, current and future analysis based on patent text mining and technology life cycle analysis. (15th December 2022) - Pan, Zhou; Wang, Yuan; Ren, Jingzheng; Chen, Hong; Lu, Yaling; Wang, Yanwei; Ping, Liying; Yang, Chenbo
Abstract: Volatile organic compounds (VOCs) pollution is a great challenge for air environment management. However, macro quantitative research on VOC control technologies (VOCTs) evolution and global knowledge transfer is still lacking. Therefore, we analyzed the 6, 636 global patents for VOCTs from 1961 to 2020 in the Derwent Innovation Index database to give a quantitative study, by using patent analysis methods such as text mining and technology life cycle analysis. The results showed that global patents surged from 2014 to 2018, and China held the most patents, followed by the US. Chinese 2013–2017 intensive atmospheric environment governance policy was the main possible reason for the sharp increase of VOC patents. However, very few Chinese patents were transferred. On the contrary, the US was the most important source country for transferred patents, and its main overseas markets were Europe, followed by China. Up to now, absorption and adsorption were the most mature technologies, accounting for 51% of the end-of-pipe patent. Biodegradation and membrane separation patents were active in transfer, indicating their high demand in the global market, so they may be promising technologies in the future. These findings enrich the literature on the evolution and transnational diffusion of VOCTs, and help policy-makers, scholars, and company managers better understand future research directions and the demands of the international market. Graphical abstract: Image 1 Highlights: Global 6, 636 patents in 1961–2020 on VOCTs were evaluated quantitively. The U.S. had the strongest VOCTPs market ties with Europe, followed by the U.S. with China. Over half (51%) of the VOCTPs for end-of-pipe focused on adsorption and absorption. The technologies of biodegradation and membrane separation were promising directions.